A PP material with scratch resistance and preparation method thereof
By using modified talc and functional auxiliary agents in PP materials, the problem of scratching scratch resistance and antibacterial performance of PP materials has been solved, and the scratching and antibacterial performance of the material is significantly improved, which is suitable for the field of car plastic.
Patent Information
- Application Number
- CN202411580101.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-07
AI Technical Summary
The existing PP materials have poor scratch resistance, are susceptible to scratches from sharp objects, and have poor antibacterial properties, which affects the use of materials and human health.
By mixing the polypropylene resin and modified talc powder, auxiliary, and cause, mix and mix together in the dual screw extruder, prepare PP materials with scratch resistance. Modified talcum powder is modified by sodium sodium, which improves its surface hydrophobicity and compatibility. The aid molecules contain a variety of functional groups to enhance the antibacterial and chemical resistance of the material.
It significantly improves the scratch and scratch resistance and antibacterial performance of PP materials, and makes it have important application value in the field of vehicle plastic.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polypropylene materials, and in particular relates to a PP material with scratch resistance and a preparation method thereof. Background Art
[0002] In recent years, my country's automobile industry has developed rapidly, and higher requirements have been put forward for its lightness, high comfort, safety, and the aesthetics, durability, environmental protection and energy saving of automotive materials. There are more and more plastic parts for automobiles. A car uses about 300kg of plastic, accounting for about 20% of the total weight of the car, among which PP, ABS, PA and other materials are used the most. As one of the lightest general-purpose plastics today, PP material is not only light in weight and relatively cheap, but also has good chemical corrosion resistance, heat resistance, balanced mechanical properties and excellent processability. It stands out among many automotive plastics and has become the largest and fastest growing automotive plastic. Its wide application in vehicles is due to its excellent heat resistance, strong rigidity, corrosion resistance and good processability.
[0003] Automotive plastics have high requirements for aesthetics and durability, but PP has low surface hardness and poor scratch resistance. It is easily scratched by sharp objects, leaving scratches, which not only affects the appearance, but also causes stress concentration in the material, limiting the application field of PP materials. Improving the smoothness of the material surface and reducing the surface friction coefficient can improve the scratch resistance of polypropylene materials. However, common amide scratch-resistant agents are small molecule additives, which degrade and precipitate under the action of light and heat, causing the surface to become sticky and affecting scratch resistance. In addition, automotive plastics often come into contact with the human body, and PP materials have poor antibacterial properties. Various bacteria are easy to grow on their surface, which will not only cause great damage to the material itself, but also endanger human health. Therefore, based on the above problems, it is urgent to invent a PP material with antibacterial and scratch-resistant properties to meet the higher demands in the field of automotive plastic technology. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a PP material with scratch resistance and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A method for preparing a PP material with scratch resistance comprises the following steps:
[0007] After the polypropylene resin is dried, it is mixed with modified talcum powder, an auxiliary agent and an initiator and then put into a twin-screw extruder for melt blending and extrusion to obtain a PP material with scratch resistance.
[0008] Furthermore, the raw materials are calculated in parts by weight as follows: 80-100 parts of polypropylene resin, 12-24 parts of modified talc, 5-15 parts of auxiliary agent, and 0.3-0.5 parts of initiator.
[0009] Furthermore, the initiator is one of benzoyl peroxide and lauroyl peroxide.
[0010] Furthermore, the modified talcum powder is prepared by the following steps:
[0011] Place sodium stearate in a three-necked flask, add n-butanol, ultrasonically dissolve it, then add talcum powder and ultrasonically vibrate it. After the vibration, place the device in an electric heating mantle, stir vigorously and heat to a constant boiling point, condense it through a condenser, and separate the n-butanol and water through a separator for the condensate. The water is discharged from the system, and the n-butanol is refluxed again. When the steam temperature reaches the boiling point of n-butanol, keep the temperature constant for 3 hours, stop heating, cool to room temperature, filter with a vacuum pump, wash with anhydrous ethanol, disperse the solid after solid-liquid separation in anhydrous ethanol, and stir. Repeat the washing for 3-5 times to obtain modified talcum powder.
[0012] Furthermore, the mesh size of the talcum powder is 3000-5000.
[0013] Furthermore, the usage ratio of sodium stearate, n-butanol and talc is 10g:100mL:2g.
[0014] The use of talcum powder with a higher mesh count can act as a heterogeneous nucleating agent in polypropylene. This change in crystal morphology reduces the scratch depth and stress whitening phenomenon of the talcum powder on the surface of the polypropylene matrix, thereby improving the surface scratch resistance of the polypropylene matrix. Moreover, by modifying it with stearic acid, its surface hydrophobicity is greatly enhanced, thereby improving the compatibility of talcum powder with the polypropylene matrix, promoting the dispersion of talcum powder in the matrix, and giving full play to the performance of the modified talcum powder, greatly enhancing the scratch resistance of the matrix.
[0015] Furthermore, the auxiliary agent is prepared by the following steps:
[0016] S1. In a three-necked flask equipped with a stirring device, triphenylphosphine (PPh3) was dissolved in toluene, chloroacetaldehyde was slowly added dropwise, and the temperature was gradually raised to 45°C. The reaction was stirred for 6 hours. After the reaction was completed, the solvent was removed by vacuum distillation to obtain intermediate 1. The ratio of triphenylphosphine, toluene and chloroacetaldehyde was 26.2g:100mL:7.8g.
[0017] Triphenylphosphine reacts with the chlorine group of chloroacetaldehyde to obtain the quaternary phosphonium product intermediate 1; the specific reaction process is as follows:
[0018] ;
[0019] S2. In a three-necked flask equipped with a stirring device, the intermediate 1 and N,N-dimethylformamide (DMF) were stirred evenly, and then diethylenetriamine and piperidine (condensing agent) were added, and the mixture was stirred evenly. The reaction temperature was controlled to be 55°C, and the reaction was kept warm for 6 hours. After the reaction was completed, part of the solvent was removed by reduced pressure distillation to obtain intermediate 2; the ratio of the amount of intermediate 1, N,N-dimethylformamide, diethylenetriamine, and piperidine was 30.5g:150mL:10.3g:15mL;
[0020] Under the action of the condensing agent, the aldehyde group on the intermediate 1 condenses with the amino group on the diethylenetriamine to form an imine group (C=N Schiff base structure). By controlling the molar ratio of the two to be close to 1:1 and the diethylenetriamine to be slightly excessive, only one amino group on the diethylenetriamine participates in the reaction to obtain the intermediate 2. The specific reaction process is as follows:
[0021] ;
[0022] S3. Add intermediate 2, pentafluoropropionic acid, dicyclohexylcarbodiimide (DCC, dehydrating agent) and N,N-dimethylformamide to a three-necked flask equipped with a stirring device, stir and mix well, place in a 55°C water bath, heat in the water bath for 8 hours, and when the reaction is finished, filter, remove the solvent by vacuum distillation, and purify by column chromatography (the eluent is a mixed solvent of benzene / ethyl acetate, the volume ratio of the two is 4:1), remove the eluent by rotary evaporation to obtain intermediate 3; the ratio of the amount of intermediate 2, pentafluoropropionic acid, dicyclohexylcarbodiimide and N,N-dimethylformamide is 38.9g:16.3g:20.6g:150mL;
[0023] Under the action of a dehydrating agent, intermediate 2 undergoes an amidation reaction with pentafluoropropionic acid to obtain intermediate 3. The specific reaction process is as follows:
[0024] ;
[0025] S4. At room temperature, in a three-necked flask equipped with a stirring device, mix the intermediate 3, 6-chloro-1-hexene, toluene and triethylamine evenly under nitrogen protection, heat to 80°C and keep the mixture for 6 hours. After the reaction is complete, filter, distill under reduced pressure, and purify by column chromatography (the eluent is a mixed solvent of benzene / ethyl acetate in a volume ratio of 5:2), remove the eluent by rotary evaporation, and dry in vacuo to obtain intermediate 4; the ratio of the amount of intermediate 3, 6-chloro-1-hexene, toluene and triethylamine is 53.6 g:11.8 g:150 mL:10 mL;
[0026] Triethylamine is used as an acid binding agent to remove the hydrogen chloride generated by the reaction, and intermediate 3 undergoes a nucleophilic substitution reaction with 6-chloro-1-hexene to obtain intermediate 4. The specific reaction process is as follows:
[0027] ;
[0028] S5. Add hydrogenated silicone oil, toluene and Speier catalyst to a three-necked flask equipped with a thermometer, a magnetron and a reflux condenser, stir at 50°C for 1 hour, add intermediate 4, heat to 80°C, keep warm for 8 hours, stop heating, stir at room temperature for 5 hours, filter and rotary evaporate to obtain an auxiliary agent; the ratio of hydrogenated silicone oil, toluene, Speier catalyst and intermediate 4 is 10g:100mL:0.5mL:15.5g; wherein the Speier catalyst is prepared by dissolving 0.1g of chloroplatinic acid in 100g of isopropanol and stirring at room temperature;
[0029] Under the catalysis of Speier catalyst, hydrogen-containing silicone oil and intermediate 4 undergo hydrosilylation reaction to obtain an additive;
[0030] ;
[0031] The prepared additive is mainly composed of polysiloxane chains, polymers with organic groups such as methyl groups connected to Si atoms, and the molecular chain presents a unique helical structure. The methyl molecules can rotate freely around the Si-O bonds. The molecular volume is large and the intermolecular force is small, which leads to the low surface energy of polysiloxane, which can effectively reduce the friction coefficient of the surface of the polypropylene matrix and enhance its scratch resistance. The additive is a large molecule, and has better migration and exudation resistance than small molecule scratch-resistant agents. In addition, the additive molecule also contains C=N Schiff base, quaternary phosphonium salt and CF bond structure, among which the C=N Schiff base structure can interact with bacterial proteins and enzymes to synthesize bacterial nucleotides and amino acids. The antibacterial activity of the matrix is improved by the introduction of quaternary phosphonium salt functional groups, in which the positively charged phosphonium ions are adsorbed on the surface of the bacteria, which can interact with the negatively charged cell membrane of the bacteria, penetrate the cell wall, combine with the cell membrane, destroy the surface structure of the cell, and cause the outflow of intracellular substances. The respiratory function of the bacteria stops, leading to cell death, and can act synergistically with Schiff bases to significantly enhance the antibacterial performance of the matrix, and the antibacterial activity is better than that of quaternary ammonium salts. Finally, the electronegativity of fluorine atoms, their atomic radius is small, and the atomic polarizability is low, which makes the CF bond have a shorter bond length and higher bond energy, and can coat the CC main chain, reduce the surface energy of the matrix, and improve the chemical resistance of the matrix.
[0032] Beneficial effects of the present invention:
[0033] 1. The PP material prepared by the present invention uses talcum powder with a higher mesh number, which can play the role of a heterogeneous nucleating agent and enhance the surface scratch resistance of the PP material; and by modifying the talcum powder, compared with ordinary talcum powder, the compatibility with the polypropylene matrix is better, so that its performance is fully exerted, and the scratch resistance of the matrix is greatly enhanced;
[0034] 2. The prepared additive molecules contain a variety of functional groups, which can enhance the scratch resistance, antibacterial and chemical resistance of PP materials, and have stable performance and are not easy to fall off;
[0035] Therefore, the PP material prepared by the present invention has excellent scratch resistance, stable and efficient antibacterial and chemical resistance, and has important application value in the field of automotive plastic technology. DETAILED DESCRIPTION
[0036] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Example 1
[0038] Preparation aids:
[0039] S1. In a three-necked flask equipped with a stirring device, 26.2 g of triphenylphosphine was dissolved in 100 mL of toluene, 7.8 g of chloroacetaldehyde was slowly added dropwise, and the temperature was gradually increased to 45°C. The reaction was stirred for 6 hours. After the reaction was completed, the solvent was removed by reduced pressure distillation to obtain intermediate 1;
[0040] S2. In a three-necked flask equipped with a stirring device, 30.5 g of intermediate 1 and 150 mL of N,N-dimethylformamide were stirred evenly, and then 10.3 g of diethylenetriamine and 15 mL of piperidine were added, and the mixture was stirred evenly. The reaction temperature was controlled to 55° C. and the reaction was kept warm for 6 hours. After the reaction was completed, part of the solvent was removed by reduced pressure distillation to obtain intermediate 2;
[0041] S3, in a three-necked flask equipped with a stirring device, add 38.9g of intermediate 2, 16.3g of pentafluoropropionic acid, 20.6g of dicyclohexylcarbodiimide and 150mL of N,N-dimethylformamide, stir and mix well, place in a 55°C water bath, heat in the water bath for 8h, and when the reaction is finished, filter, remove the solvent by vacuum distillation, and purify by column chromatography (the eluent is a mixed solvent of benzene / ethyl acetate, the volume ratio of the two is 4:1), and remove the eluent by rotary evaporation to obtain intermediate 3;
[0042] S4, at room temperature, under nitrogen protection, in a three-necked flask equipped with a stirring device, 53.6 g of intermediate 3, 11.8 g of 6-chloro-1-hexene, 150 mL of toluene and 10 mL of triethylamine were mixed evenly, and the temperature was raised to 80°C for 6 hours of insulation. After the reaction was completed, the mixture was filtered, evaporated under reduced pressure, and purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate in a volume ratio of 5:2), the eluent was removed by rotary evaporation, and vacuum dried to obtain intermediate 4;
[0043] S5. In a three-necked flask equipped with a thermometer, a magnet and a reflux condenser, 10 g of hydrogenated silicone oil, 100 mL of toluene and 0.5 mL of Speier catalyst (prepared by dissolving 0.1 g of chloroplatinic acid in 100 g of isopropanol and stirring at room temperature) were added. After stirring at 50°C for 1 h, 15.5 g of intermediate 4 was added. The temperature was raised to 80°C. After keeping the temperature for 8 h, the heating was stopped. After stirring at room temperature for 5 h, the mixture was filtered and rotary evaporated to obtain an auxiliary agent.
[0044] Example 2
[0045] Preparation aids:
[0046] S1. In a three-necked flask equipped with a stirring device, 52.4 g of triphenylphosphine was dissolved in 200 mL of toluene, 15.6 g of chloroacetaldehyde was slowly added dropwise, and the temperature was gradually increased to 45°C. The reaction was stirred for 6 hours. After the reaction was completed, the solvent was removed by reduced pressure distillation to obtain intermediate 1;
[0047] S2. In a three-necked flask equipped with a stirring device, 61.0 g of intermediate 1 and 300 mL of N,N-dimethylformamide were stirred evenly, and then 20.6 g of diethylenetriamine and 30 mL of piperidine were added, and the mixture was stirred evenly. The reaction temperature was controlled to 55° C. and the reaction was kept warm for 6 hours. After the reaction was completed, part of the solvent was removed by reduced pressure distillation to obtain intermediate 2;
[0048] S3, in a three-necked flask equipped with a stirring device, add 77.8g of intermediate 2, 32.6g of pentafluoropropionic acid, 41.2g of dicyclohexylcarbodiimide and 300mL of N,N-dimethylformamide, stir and mix well, place in a 55°C water bath, heat in the water bath for 8h, and when the reaction is finished, filter, remove the solvent by vacuum distillation, and purify by column chromatography (the eluent is a mixed solvent of benzene / ethyl acetate, the volume ratio of the two is 4:1), and remove the eluent by rotary evaporation to obtain intermediate 3;
[0049] S4, at room temperature, under nitrogen protection, in a three-necked flask equipped with a stirring device, 107.2 g of intermediate 3, 23.6 g of 6-chloro-1-hexene, 300 mL of toluene and 20 mL of triethylamine were mixed evenly, and the temperature was raised to 80°C for 6 hours of insulation. After the reaction was completed, the mixture was filtered, evaporated under reduced pressure, and purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate in a volume ratio of 5:2), the eluent was removed by rotary evaporation, and vacuum dried to obtain intermediate 4;
[0050] S5. In a three-necked flask equipped with a thermometer, a magnet and a reflux condenser, 20 g of hydrogenated silicone oil, 200 mL of toluene and 1 mL of Speier catalyst (prepared by dissolving 0.1 g of chloroplatinic acid in 100 g of isopropanol and stirring at room temperature) were added. After stirring at 50°C for 1 h, 31 g of intermediate 4 was added. The temperature was raised to 80°C. After keeping the temperature for 8 h, the heating was stopped. After stirring at room temperature for 5 h, the mixture was filtered and rotary evaporated to obtain an auxiliary agent.
[0051] Example 3
[0052] Preparation of modified talc:
[0053] Place 10g of sodium stearate in a three-necked flask, add 100mL of n-butanol, and after ultrasonic dissolution, add 2g of talcum powder with a mesh size of 3000 and ultrasonically vibrate. After vibration, place the device in an electric heating mantle, stir vigorously and heat to a constant boiling point, condense through a condenser, and separate the n-butanol and water through a separator for the condensate. The water is discharged from the system, and the n-butanol is refluxed again. When the steam temperature reaches the boiling point of n-butanol, keep the temperature constant for 3h, stop heating, cool to room temperature, filter with a vacuum pump, wash with anhydrous ethanol, disperse the solid after solid-liquid separation in anhydrous ethanol, and stir. Repeat this washing 3 times to obtain modified talcum powder.
[0054] Example 4
[0055] Preparation of modified talc:
[0056] Place 20g of sodium stearate in a three-necked flask, add 200mL of n-butanol, and after ultrasonic dissolution, add 4g of talc with a mesh size of 5000 and ultrasonically vibrate. After vibration, place the device in an electric heating mantle, stir vigorously and heat to a constant boiling point, condense through a condenser, and separate the n-butanol and water through a separator for the condensate. The water is discharged from the system, and the n-butanol is refluxed again. When the steam temperature reaches the boiling point of n-butanol, keep the temperature constant for 3h, stop heating, cool to room temperature, filter with a vacuum pump, wash with anhydrous ethanol, disperse the solid after solid-liquid separation in anhydrous ethanol, and stir. Repeat this washing 5 times to obtain modified talc.
[0057] Example 5
[0058] 80 g of polypropylene resin was placed in a constant temperature drying oven at 70° C. and dried for 24 h. Then, it was mixed with 12 g of the modified talc prepared in Example 3, the auxiliary agent prepared in Example 1 and 0.3 g of lauroyl peroxide and put into a twin-screw extruder for melt blending and extrusion to obtain a PP material with scratch resistance.
[0059] Example 6
[0060] 90 g of polypropylene resin was placed in a constant temperature drying oven at 75° C. and dried for 36 h. Then, it was mixed with 18 g of the modified talc prepared in Example 3, the auxiliary agent prepared in Example 1 and 0.4 g of benzoyl peroxide and put into a twin-screw extruder for melt blending and extrusion to obtain a PP material with scratch resistance.
[0061] Example 7
[0062] 100 g of polypropylene resin was placed in a constant temperature drying oven with a blast oven at 80° C. and dried for 48 h. The mixture was mixed with 24 g of the modified talc prepared in Example 3, the auxiliary agent prepared in Example 1 and 0.5 g of benzoyl peroxide and then put into a twin-screw extruder for melt blending and extrusion to obtain a PP material with scratch resistance.
[0063] Comparative Example 1
[0064] The auxiliary agent in Example 7 was replaced by an amide anti-scratch agent of equal mass, and the remaining steps were the same as those in Example 7.
[0065] Comparative Example 2
[0066] Use commercially available scratch-resistant PP material.
[0067] Examples 5-7 and Comparative Examples 1-2 were made into corresponding shapes according to different test standards and the following performance tests were performed:
[0068] The scratch resistance was tested on an electric cross-hatch tester according to Volkswagen PV3952 standard. The test conditions were: load 10N, test speed 1000mm / min, cross-hatch 20x2mm, blade 1mm. After scratching, the samples were stored at standard pressure for 48h. The color difference ΔL of the scratches before and after 180 days was tested with a spectrophotometer.
[0069] The national standard GB / T 1040.2-2006 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics" was used to measure the tensile properties of the samples before and after alkali treatment, acid treatment, and water treatment, and the tensile strength retention rate was calculated; tensile strength retention rate = tensile strength after test / tensile strength before test × 100%;
[0070] Alkali treatment: sodium hydroxide solution with a pH value of 13 in a 55°C water bath for 4 hours;
[0071] Acid treatment: hydrochloric acid solution with a pH value of 2 in a water bath at 55°C for 4 hours;
[0072] The antibacterial rate of Staphylococcus aureus and Escherichia coli was measured using QB / T 2591-2003A "Test methods and antibacterial effects of antibacterial plastics";
[0073] The measured results are shown in the following table:
[0074] ;
[0075] It can be seen from the above table that the PP material prepared in the embodiment of the present invention has excellent scratch resistance, stable and efficient antibacterial and chemical resistance, and has important application value in the field of automotive plastic technology.
[0076] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0077] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing a PP material with scratch resistance, characterized in that: The following steps are involved: After the polypropylene resin is dried, it is mixed with modified talcum powder, an additive and an initiator and then put into a twin-screw extruder for melt blending and extrusion to obtain a PP material with scratch resistance; Wherein, the initiator is one of benzoyl peroxide and lauroyl peroxide; Wherein, the auxiliary agent is prepared by the following steps: S1, dissolving triphenylphosphine in toluene, slowly adding chloroacetaldehyde, and gradually raising the temperature to 45°C, stirring and reacting for 6 hours, and after the reaction is completed, distilling under reduced pressure to obtain intermediate 1; S2, the intermediate 1 and N, N-dimethylformamide were stirred evenly, diethylenetriamine and piperidine were added, stirred and mixed, reacted at 55° C. for 6 h, and after the reaction was completed, vacuum distillation was performed to obtain the intermediate 2; S3, after mixing the intermediate 2, pentafluoropropionic acid, dicyclohexylcarbodiimide and N,N-dimethylformamide, the mixture was heated at 55°C for 8 hours, the reaction was completed, and the mixture was filtered, distilled under reduced pressure, purified by column chromatography, and rotary evaporated to obtain the intermediate 3; S4, at room temperature, under nitrogen protection, the intermediate 3, 6-chloro-1-hexene, toluene and triethylamine were mixed evenly, reacted at 80°C for 6 hours, and after the reaction was completed, filtered, distilled under reduced pressure, purified by column chromatography, rotary evaporated, and vacuum dried to obtain intermediate 4; S5. Stir hydrogenated silicone oil, toluene and Speier catalyst at 50°C for 1 hour, then add intermediate 4, raise the temperature to 80°C, keep the temperature for reaction for 8 hours, stop heating, stir at room temperature for 5 hours, filter and rotary evaporate to obtain an auxiliary agent.
2. The method for preparing a PP material with scratch resistance according to claim 1, characterized in that: The raw materials are calculated in parts by weight as follows: 80-100 parts of polypropylene resin, 12-24 parts of modified talc, 5-15 parts of auxiliary agent, and 0.3-0.5 parts of initiator.
3. The method for preparing a PP material with scratch resistance according to claim 1, characterized in that: In step S1, the ratio of triphenylphosphine, toluene and chloroacetaldehyde is 26.2 g:100 mL:7.8 g.
4. The method for preparing a PP material with scratch resistance according to claim 1, characterized in that: In step S2, the ratio of the amount of intermediate 1, N,N-dimethylformamide, diethylenetriamine and piperidine is 30.5 g:150 mL:10.3 g:15 mL.
5. The method for preparing a PP material with scratch resistance according to claim 1, characterized in that: In step S3, the ratio of the amount of intermediate 2, pentafluoropropionic acid, dicyclohexylcarbodiimide, and N,N-dimethylformamide is 38.9 g:16.3 g:20.6 g:150 mL.
6. The method for preparing a PP material with scratch resistance according to claim 1, characterized in that: In step S4, the ratio of the amount of intermediate 3, 6-chloro-1-hexene, toluene and triethylamine is 53.6 g:11.8 g:150 mL:10 mL.
7. The method for preparing a PP material with scratch resistance according to claim 1, characterized in that: In step S5, the ratio of the amount of hydrogen-containing silicone oil, toluene, Speier catalyst, and intermediate 4 is 10 g: 100 mL: 0.5 mL: 15.5 g.
8. The method for preparing a PP material with scratch resistance according to claim 1, characterized in that: Modified talc is prepared by the following steps: Place sodium stearate in a flask, add n-butanol, ultrasonically dissolve it, then add talcum powder and ultrasonically shake it. After shaking, stir it vigorously and heat it to a constant boiling point. Condensate it through a condenser to separate the n-butanol and water. The water is discharged from the system and the n-butanol is refluxed. When the steam temperature reaches the boiling point of n-butanol, keep the temperature constant for 3 hours, stop heating, cool, filter and wash. Disperse the solid after solid-liquid separation in anhydrous ethanol and stir it. Repeat this washing to obtain modified talcum powder.
9. A PP material with scratch resistance, characterized in that: Prepared according to the method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Process for preparing antibacterial high-strength material special for automotive trim granulation
CN115651309A
Flame-retardant phenolic moulding plastic and preparation method thereof
CN118755230A